2018
DOI: 10.1007/s10484-018-9410-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Cognitive Rehabilitation and Neurofeedback on Sustained Attention Among Elementary School Students with Specific Learning Disorder: A Preliminary Randomized Controlled Clinical Trial

Abstract: Specific learning disorder (SLD) can occur along with the problems of attention performance and be complicated by them. Recent studies have reported the positive effects of cognitive rehabilitation (CR) and neurofeedback (NFB) on sustained attention (SA) in SLD. Nevertheless, it has not yet been determinedwhat kind of treatment may be the most appropriate option for this disorder in terms of the different functions of cognitive status, especially SA. This preliminary study aimed to compare CR and NFB effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We found that the odds of moving toward the standard value was greater than the odds of moving outside the standard values after treatment, which is in line with previous studies (Pérez-Elvira et al, 2018;Pérez-Elvira, et al, 2019) reporting that there is little likelihood for z-scores to move out of the normal range due to the LZT intervention. Some authors (Azizi et al, 2018) have concluded that NF is not effective for LD. They compared NF with cognitive rehabilitation for LD, but their study has some methodological limitations.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the odds of moving toward the standard value was greater than the odds of moving outside the standard values after treatment, which is in line with previous studies (Pérez-Elvira et al, 2018;Pérez-Elvira, et al, 2019) reporting that there is little likelihood for z-scores to move out of the normal range due to the LZT intervention. Some authors (Azizi et al, 2018) have concluded that NF is not effective for LD. They compared NF with cognitive rehabilitation for LD, but their study has some methodological limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Initially used for brain-damaged patients, CR use was extended to schizophrenia ( 13 ), and later to several pediatric mental health conditions. CR effectiveness was demonstrated in children and adolescents with attention deficit hyperactivity disorder (ADHD) ( 14 ), anorexia nervosa ( 15 , 16 ), specific learning disorder ( 17 ), intellectual disability ( 18 ) and in early onset psychosis ( 19 ).…”
Section: Effects Of Cr In Children and Adolescents With Asdmentioning
confidence: 99%
“…SLDs encompass difficulties with listening, speaking, reading, spelling or doing mathematical calculations. Reading, writing and mathematics skills are key academic skills (Azizi et al, 2018), the foundation for other academic learning (Abdelraouf et al, 2018). The main symptoms that can also interfere with independent learning required at university level can be poor short-term memory (Kavale & Flanagan, 2007), attention deficits (Marzocchi et al, 2009), difficulty in academic and learning tasks (Esmaili et al, 2016), poor motor skills and motor-related daily functions (Tal-Saban & Weintraub, 2019), inefficient planning and organization (Hendriksen et.al., 2007), processing problems (Cornoldi et al, 2019), difficulties in organizing information and developing learning and cognitive skills (Shenoy, 2016), challenging access to the constant cognitive effort necessary for the rote learning of facts, figures and procedural rules (Savidis et al, 2007), IQ-achievement discrepancy between potential and achievement, significant gap between the true potential and the day to day performance (Kulkarni et al, 2001), disruptive behaviors (Chatzara et al, 2014), despite age-appropriate instruction, long-term remedial efforts (Kirk, 1962;Addison Stone, 1980), normal intelligence, motivation to learn, adequate socio-cultural and learning opportunity (Wang & Chung, 2021).…”
Section: Specific Learning Disorders In the Context Of Higher And Adu...mentioning
confidence: 99%